Second nature - Hoffman, Alice 1952- (Putnam, 1994)
Robin begins to realize the intricacy of what it means to be human when she rescues an innocent man mistaken for a beast and takes him home with her.
Keywords: Community life -- Fiction; Islands -- Fiction; Wild men -- Fiction; Fiktionale Darstellung